Peran Manajemen SDM dalam Meningkatkan Produktivitas dan Keberlanjutan Usaha Perikanan - Andalangi Maatuil, Rexy; Belicia Caroles; Kinanty Mewal (Indo Publishing, 2025)
This study examines the management of human resources (HR) in the fisheries sector, which plays a significant role in Indonesia’s national economic growth. Although the country has substantial marine potential, HR management in this sector still faces various challenges, including limited worker competency, insufficient technology‐based training, and weak supervisory and organizational systems. Using a descriptive method complemented by a literature review, this research analyzes factors influencing HR quality and identifies strategies that can enhance overall fisheries sector performance. The findings reveal that worker competency, technological readiness, and supportive government policies are key determinants of effective HR management. In addition, collaboration among government agencies, educational institutions, community organizations, and industry players is crucial to strengthening competitiveness. The synthesis of the discussion highlights that sustainable HR development through continuous training, digital skill improvement, and structured management practices is essential for ensuring that the fisheries sector remains competitive and contributes optimally to Indonesia’s long-term national development.